Synthesis of well-defined α, ω-telechelic multiblock copolymers in aqueous medium: in situ generation of α, ω-diols1. Issue 12 (28th March 2015) - Simula, Alexandre; Nikolaou, Vasiliki; Anastasaki, Athina; Alsubaie, Fehaid; Nurumbetov, Gabit; Wilson, Paul; Kempe, Kristian; Haddleton, David M.
<x xml:space="preserve">Abstract</x> The synthesis of well-defined α, ω-dihydroxyl telechelic multiblock copolymers by sequential in situ chain extensions via aqueous Cu(0) mediated living radical polymerization (SET-LRP) is reported.